PENGARUH BRAND IMAGE DAN PERSEPSI KUALITAS TERHADAP MINAT BELI KONSUMEN SMARTPHONE OPPO PADA TOKO HELMIUS PONSEL KABUPATEN NIAS SELATAN - dohude, Kurniawati (LPPM Universitas Nias Raya, 2023)
The purpose of this study is to determine the influence of brand image and quality perception on the buying interest of Oppo Smartphone consumers at the South Nias Regency Mobile Phone Helmius Store. The type of research is the quantitative type. The population and sample in this study were as many as 36 respondents This type of research data is a type of primary data, namely data obtained directly from respondents. The source of this research data is from consumers by using questionnaires. The data analysis method used is multiple regression analysis. Based on the results of the study, it was determined that there was an influence of brand image and quality perception on the buying interest of Oppo Smartphone consumers at the South Nias Regency Mobile Phone Helmius Store simultaneously. The suggestions of this study are (1) To increase consumer buying interest, every Oppo product should be given a discounted price so that it can explore consumer attention to have it. (2) Helmius Store should group quality products with products that are not suitable for consumption to maintain consumer expectations of trust in the product.